2010
DOI: 10.4319/lo.2010.55.3.1377
|View full text |Cite
|
Sign up to set email alerts
|

Generalizations of the Wedderburn number: Parameterizing upwelling in stratified lakes

Abstract: The effect of lake geometry on wind-induced upwelling, in a two-layer stratified lake with a variable bottom slope and generic planar shape is investigated. (1) The traditional linearized classification parameter for upwelling, the Wedderburn number, is extended to include finite amplitude effects in a rectangular basin; this extension is important when the Wedderburn number is , , 3. (2) The Wedderburn number is generalized to incorporate the influence of a bottom slope and a variable-width basin for both the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 35 publications
(45 reference statements)
2
57
0
Order By: Relevance
“…The main parameters characterizing the system during the two storms are given in Table 3. The value of W 21 between 0.45 and 0.91 (see Table 3) was such that the theory of Shintani et al (2010) suggests upwelling; that of Horn et al (2001) implies that both wind event responses fall into regime 2, with the basin-scale waves degenerating into solitary waves by nonlinear steepening.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The main parameters characterizing the system during the two storms are given in Table 3. The value of W 21 between 0.45 and 0.91 (see Table 3) was such that the theory of Shintani et al (2010) suggests upwelling; that of Horn et al (2001) implies that both wind event responses fall into regime 2, with the basin-scale waves degenerating into solitary waves by nonlinear steepening.…”
Section: Resultsmentioning
confidence: 99%
“…The degeneration of weakly nonlinear, basin-scale Kelvin and Poincaré waves has recently been investigated by de la Fuente et al (2008Fuente et al ( , 2010 using a weakly nonhydrostatic model. These authors found Kelvin waves steepened, shedding solitary-type waves similarly to the nonrotating case, whereas Poincaré waves lost their symmetry reversibly as nonlinearities increased, exchanging energy with submodes.…”
mentioning
confidence: 99%
“…The situation changes when the thermocline tilt becomes significant, i.e. when the thin interface between epilimnion and hypolimnion reaches the lake surface at its margins (Shintani et al, 2010). In this case it is the term ∂(w f )/∂z that accounts for the eventual lake overturn, i.e.…”
Section: The Generic 1-d Equation and Vertical Coordinatementioning
confidence: 99%
“…complete vertical homogenization of a water body. This process cannot be simulated by 1-D lake models explicitly, but may be diagnosed using Wedderburn (Shintani et al, 2010) and Lake numbers (Imberger and Patterson, 1989). Here, when applying the lake model for the lake under study, we will use Wed-derburn number time series to check the validity of dropping out the "vertical circulation term" 1 .…”
Section: The Generic 1-d Equation and Vertical Coordinatementioning
confidence: 99%
See 1 more Smart Citation